Contrasting spatial patterns in the diurnal and semidiurnal temperature variability in the Santa Barbara Channel, California. Issue 1 (11th January 2016) - Aristizábal, María F.; Fewings, Melanie R.; Washburn, Libe
Abstract: The Santa Barbara Channel, California, experiences large temperature fluctuations during summer that have been associated with the input of nutrients to the euphotic zone. We studied the temperature fluctuations in the diurnal and semidiurnal bands, which account for as much as 65% of the total variance. We analyzed data from 25 moorings along the mainland and the Northern Channel Islands deployed at depths 8–18 m during 1999–2012. In the diurnal band, the temperature fluctuations vary almost simultaneously within two distinct regions, with a lag of 5 h between the regions: the mainland east of Point Conception and the west part of the Channel exposed to the large‐scale winds. The two regions of in‐phase temperature variability are in agreement with a previously published division of zones according to the wind characteristics. The portion of the diurnal temperature variance that is wind driven does not propagate along the coastline, but rather is directly forced by the wind. The semidiurnal temperature oscillations are more substantial in the Northern Channel Islands. These findings are consistent with a numerical study that predicted that the steep slopes of the Santa Cruz Basin, located south of the Channel Islands, are a source of semidiurnal internal tides. We conclude that the contrast between the spatial patterns of the diurnal and semidiurnal temperature oscillations on scales of tens of kilometers reflects the spatial distribution of the main forcing in each band, namely the diurnal wind and the locally generated semidiurnal internal tide. The spatial patterns of the diurnal and semidiurnal oscillations reflect the forcing in each band. Key Points: Diurnal and semidiurnal temperature oscillations are forced by the sea breeze and the internal tide Diurnal temperature oscillations do not propagate along shore but are directly forced by the wind The spatial patterns of the diurnal and semidiurnal oscillations reflect the forcing in each band